Architect Herman Bollé and German Neo-Renaissance in Croatian Architecture in the Late 19th Century - Damjanović, Dragan (Array, 2013)
In the late 1870s the dominance of the Italian Neo-Renaissance style in Croatian residential and public architecture and the Gothic style in church architecture was superseded by the German Neo-Renaissance style introduced by architect Herman Bollé. Characterized by architectural quality and picturesqueness his German Neo-Renaissance buildings represented a reflection of the European architectural developments in Croatia.